2021
DOI: 10.1002/ame2.12168
|View full text |Cite
|
Sign up to set email alerts
|

Novel spontaneous myelodysplastic syndrome mouse model

Abstract: Background Myelodysplastic syndrome (MDS) is a group of disorders involving hemopoietic dysfunction leading to leukemia. Although recently progress has been made in identifying underlying genetic mutations, many questions still remain. Animal models of MDS have been produced by introduction of specific mutations. However, there is no spontaneous mouse model of MDS, and an animal model to simulate natural MDS pathogenesis is urgently needed. Methods In characterizing the genetically diverse mouse strains of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…15,16 Susceptibility to diseases, development of the animal model, and related genetic loci mapping are being investigated increasingly in CC mice. [17][18][19] In our research, we found that different strains of GD mice exhibit an extremely wide range of variance in response to morphine analgesia, including large differences in morphine sensitivity and susceptibility of morphine tolerance.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…15,16 Susceptibility to diseases, development of the animal model, and related genetic loci mapping are being investigated increasingly in CC mice. [17][18][19] In our research, we found that different strains of GD mice exhibit an extremely wide range of variance in response to morphine analgesia, including large differences in morphine sensitivity and susceptibility of morphine tolerance.…”
Section: Introductionmentioning
confidence: 69%
“…After more than 10 years of breeding, the resulting inbred CC strains exhibit a wide range of traits and have great advantages in integrative analysis of complex systems that can be defined only in vivo, such as resistance to Ebola virus infection and variability in immunoglobulin glycosylation 15,16 . Susceptibility to diseases, development of the animal model, and related genetic loci mapping are being investigated increasingly in CC mice 17–19 . In our research, we found that different strains of GD mice exhibit an extremely wide range of variance in response to morphine analgesia, including large differences in morphine sensitivity and susceptibility of morphine tolerance.…”
Section: Introductionmentioning
confidence: 78%
“…The double-stranded PCR products were heat-denatured and circularized by the splint oligo sequence. The single-strand circle DNA (ssCir DNA) was formatted as the final library and qualified by QC 22 . The qualified libraries were sequenced on the MGISEQ-2000 platform (BGI Shenzhen, China).…”
Section: Methodsmentioning
confidence: 99%
“…Even though animal models are valuable tools for research, the expenditure is high, drug screening requires a large amount of animals and, biologically, model animals cannot completely mimic human BM microenvironments. These issues emphasize the need for better strategies to improve human systems modeling in vivo; in this context, new results and extensive reviews regarding animal models for leukemic research are periodically published [127,129,[136][137][138][139][140][141][142][143][144][145][146]. The graph is based on [129], with additional information from [145,[147][148][149].…”
Section: In Vivo Rodent Modelsmentioning
confidence: 99%